Obsessive‐Compulsive Disorder in Adults with High‐Functioning Autism Spectrum Disorder: What Does Self‐Report with the OCI‐R Tell Us?. Issue 5 (7th February 2015) - Cadman, Tim; Spain, Debbie; Johnston, Patrick; Russell, Ailsa; Mataix‐Cols, David; Craig, Michael; Deeley, Quinton; Robertson, Dene; Murphy, Clodagh; Gillan, Nicola; Wilson, C. Ellie; Mendez, Maria; et al.
<x xml:space="preserve">Abstract</x> Little is known about the symptom profile of obsessive‐compulsive disorder (OCD) in individuals who have autism spectrum disorders (ASD). It is also unknown whether self‐report questionnaires are useful in measuring OCD in ASD. We sought to describe the symptom profiles of adults with ASD, OCD, and ASD + OCD using the Obsessive Compulsive Inventory‐Revised (OCI‐R), and to assess the utility of the OCI‐R as a screening measure in a high‐functioning adult ASD sample. Individuals with ASD (n = 171), OCD (n = 108), ASD + OCD (n = 54) and control participants (n = 92) completed the OCI‐R. Individuals with ASD + OCD reported significantly higher levels of obsessive‐compulsive symptoms than those with ASD alone. OCD symptoms were not significantly correlated with core ASD repetitive behaviors as measured on the ADI‐R or ADOS‐G. The OCI‐R showed good psychometric properties and corresponded well with clinician diagnosis of OCD. Receiver operating characteristic analysis suggested cut‐offs for OCI‐R Total and Checking scores that discriminated well between ASD + versus –OCD, and fairly well between ASD‐alone and OCD‐alone. OCD manifests separately from ASD and is characterized by a different profile of repetitive thoughts and behaviors. The OCI‐R appears to be useful as a screening tool in the ASD adult population. Autism Res2015, 8: 477–485. © 2015 International Society for Autism Research, Wiley Periodicals, Inc.